Effects of the multidrug resistance-1 gene on drug resistance in primary immune thrombocytopenia. (2nd October 2016) - Liu, Wenjie; Li, Huiyuan; Zhang, Donglei; Lv, Mingen; Li, Yang; Hao, Yating; Chen, Yunfei; Liu, Xiaofan; Xue, Feng; Zhang, Lei; Yang, Renchi
Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune disorder that is characterized by low platelet count. Glucocorticoids (GCs) resistance is a great challenge in the treatment of ITP. P-glycoprotein (P-gp) is a widely studied protein, which is associated with drug resistance. However, in ITP, the functional activity and immune regulation mechanism of P-gp remain uncertain. In this study, we evaluated the expression and functional activity of P-gp in different lymphocyte subsets, explored the correlation between P-gp function and GCs resistance and investigated the role of P-gp in ITP pathogenesis. Results indicated that the functional activity and mRNA level of P-gp were significantly higher in GCs-nonresponsive patients than in GCs-responsive patients with ITP. However, these differences in P-gp were only significant in CD8 + T cells. P-gp function was related to disease activity rather than GCs therapy. P-gp was involved in secreting granzyme B and perforin, maintaining autoreactive lymphocytes survival and enhancing autologous platelets lysis in ITP. In conclusion, over-functional P-gp might play an important role in the pathogenesis of ITP and induce GCs resistance in nonresponsive ITP patients. The blockage of P-gp could be a promising therapeutic approach for GCs-resistant patients with ITP.